2018
DOI: 10.3390/min8120577
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Petrographic Characteristics and Physico-Mechanical Properties of Aggregates on the Quality of Concrete

Abstract: This paper examines the effect of the aggregate type on concrete strength, and more specifically, how the petrographic characteristics of various aggregate rocks as well as their physicomechanical properties influences the durability of C 25/30 strength class concrete. The studied aggregate rocks were derived from Veria-Naousa and Edessa ophiolitic complexes as well as granodiorite and albitite rocks from their surrounding areas in central Macedonia (Greece). Concretes were produced with constant volume propor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 32 publications
(56 reference statements)
0
36
0
4
Order By: Relevance
“…The diagram in Figure 6c illustrates the interaction of the mechanical properties LA and UCS directly dependent on the grain size. Several researchers have also reported similar relationships between these properties [23,65,69,70] when studying various types of rocks. In this diagram, it seems obvious that the mechanical characteristics of sandstones vary in a similar way under different type of mechanical loadings.…”
Section: The Impact Of Petrographic Characteristics On the Sandstone mentioning
confidence: 64%
See 2 more Smart Citations
“…The diagram in Figure 6c illustrates the interaction of the mechanical properties LA and UCS directly dependent on the grain size. Several researchers have also reported similar relationships between these properties [23,65,69,70] when studying various types of rocks. In this diagram, it seems obvious that the mechanical characteristics of sandstones vary in a similar way under different type of mechanical loadings.…”
Section: The Impact Of Petrographic Characteristics On the Sandstone mentioning
confidence: 64%
“…These satisfactory strength results may attributed to the generally high microtopography of coarse-grained, medium-grained, as well as of fine-grained sandstones relative to the microtopography of other used rocks [22] (Figure 2b,d,f,h and Figure 4). The microtopography of the aggregates constitutes a crucial factor for the mechanical quality of the aggregate rocks and consequently for the quality of the produced concrete as it influences the cohesion and the bonding between the cement paste and the aggregate particles [1,22,23]. The only studied concrete specimen that displays lower strength (25 MPa) than the standard states is the specimen in which the used aggregate was the enriched in carbonate fossils coarse grained sandstone (Figure 2c).…”
Section: The Impact Of Petrographic Characteristics On the Sandstone mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, several researchers, such as Rigopoulos et al [62], have studied the effect of microroughness of various rocks and how it affects their quality as aggregates according to the BS 812 Part 1 [58]. More specifically, Petrounias et al [56,63] who studied various rocks on their suitability as concrete aggregates reported that the microroughness of the aggregate particles plays a determinant role in the quality of the concrete products. Smooth surface constitute determinant negative factor for poor bonding of the aggregate grain and the cement paste and, hence, low concrete strength.…”
Section: Methodsmentioning
confidence: 99%
“…Serpentinite comprises abundant and extensive outcrops in several ophiolite complexes in Greece and worldwide, and so therefore its use to remediate analogous quagmires is cost effective. For example, in the Veria-Naousa, ophiolite occurs near the studied Agios Philippos polluted pit lake [20][21][22][23][24]. Furthermore, magnesite has been widely used from several researchers for the remediation of industrial waste waters.…”
Section: Introductionmentioning
confidence: 99%